Teacher perceived difficulty in implementing differentiated instructional strategies in primary school. Issue 5 (4th May 2017) - Gaitas, Sérgio; Alves Martins, Margarida
ABSTRACT: This study analyses teacher perceived difficulty in implementing differentiated instructional strategies in regular classes. The participants were 273 Portuguese primary school teachers with teaching experience ranging from 1 to 33 years. A 39-item questionnaire was used to evaluate teacher perceived difficulty in relation to different instructional strategies. Teacher responses were factor analysed and five different domains were identified: (1) activities and materials; (2) assessment; (3) management; (4) planning and preparation; and (5) classroom environment. Results showed that with the exception of the classroom environment domain, all the instruction practices in the remaining domains were considered to be difficult. In particular, the most difficult practices were under the domain of activities and materials and were associated with the adaptation of curricular elements (content, process, and product) based on student characteristics (readiness, interest, and learning profiles). The results also revealed a strong association between the activities and materials domain and the assessment domain. Some implications of these findings for initial teacher training and teacher professional development programmes are discussed.